2001
DOI: 10.1097/00042737-200104000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Gastric corpus atrophy following eradication of Helicobacter pylori

Abstract: Corpus atrophy as defined by the Sydney System is reversible in some patients after H. pylori eradication. Improvement in atrophy is associated with a fall in fasting plasma gastrin levels. This may have implications in the prevention of gastric carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Hojo et al (10), in their recent review article, indicated that atrophy and IM generally did not improve among all patients and that disagreement between the studies was not totally due to the sample size or follow-up period. Various sample sizes of 5, 20, 22, 40, and 163 patients (14,6,7,12,8) and follow-up periods of 5, 6, 12, 48, and 60 months (14,12,8,7,6) have been reported. According to Satoh et al (6), some reports showed that the grades of body atrophy decreased significantly after eradication, while others showed no change, indicating that this disagreement might be related to the grade of atrophy, mild, moderate, or severe, before treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hojo et al (10), in their recent review article, indicated that atrophy and IM generally did not improve among all patients and that disagreement between the studies was not totally due to the sample size or follow-up period. Various sample sizes of 5, 20, 22, 40, and 163 patients (14,6,7,12,8) and follow-up periods of 5, 6, 12, 48, and 60 months (14,12,8,7,6) have been reported. According to Satoh et al (6), some reports showed that the grades of body atrophy decreased significantly after eradication, while others showed no change, indicating that this disagreement might be related to the grade of atrophy, mild, moderate, or severe, before treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies reported on H. pylori eradication and follow-up in the last 5 years were from Japan (6)(7)(8)(9)(10) and the others were single studies from Western countries (11)(12)(13)(14)(15). From these studies, discrepancies among the results were noticed and it was concluded that atrophy and IM were reversible only in some patients regardless of the sample size and the follow-up period.…”
mentioning
confidence: 99%
“…Moreover, it should be noted that 20 out of 21 studies demonstrated the reduced level of serum gastrin by H. pylori eradication therapy, suggesting improvement of inflammation in the corpus (table 2) [18, 19, 21, 22,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49]. The level of somatostatin and the number of D cells have been reported to increase after therapy [38, 45,][50], although this requires biopsy specimens for the estimation.…”
Section: Pepsinogen Gastrin and Gastric Acid Secretionmentioning
confidence: 99%
“…A long term study with five year follow up from China have reported no change in the degree of intestinal metaplasia (IM) and atrophy after successful eradication [3]. In other long term randomized controlled trials there was a significant regression of preneoplastic lesions such as atrophy and IM among those who had cleared the infection after five to six years of follow up [4,5]. A definite cure of peptic ulcer disease and prevention of ulcer complications, as well as cure of mucosa-associated lymphoid tissue (MALT) lymphoma is dependent on successful eradication of H. pylori .…”
Section: Introductionmentioning
confidence: 99%